THE EFFECT OF USING THE TEAM GAMES TOURNAMENT TYPE COOPERATIVE MODEL USING CHAIN QUESTION CARD MEDIA ON MATHEMATICS LEARNING IN GRADE V STATE ELEMENTARY SCHOOL 102/II SUNGAI KERJAN - Ailiya, Natasea (FKIP Universitas Muhammadiyah Tangerang, 2025)
AbstractThis research was motivated by the low mathematics learning outcomes of fifth-grade students at SD Negeri 102/II Sungai Kerjan. As many as 46% of students had not achieved the Learning Objective Completion Criteria (KKTP), indicating the need for the implementation of innovative and enjoyable learning models. The purpose of this study was to determine the effect of using chained question cards in the Team Games Tournament (TGT) cooperative learning model on students' mathematics learning outcomes. This study used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design. The study sample consisted of two classes: an experimental class of 26 students who received the TGT model using chained question cards, and a control class of 24 students who were taught conventionally. The instruments used were pre-tests and post-tests. Data were analyzed using the non-parametric Mann-Whitney test because the data were not normally distributed. The analysis showed a significant difference between the post-test scores of students in the experimental and control classes. The average learning outcomes of students in the experimental class were higher than those in the control class. The hypothesis test showed a significance value (p-value) <0.05, thus the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that the use of chained question cards in the Team Games Tournament (TGT) cooperative learning model significantly improved fifth-grade students' mathematics learning outcomes.Keywords: team games tournament (TGT), chained question cards, mathematics learning outcomes, cooperative learning.